THE FACTOR WHICH INFLUENCE IT INFRASTRUCTURE: SOFTWARE, IT FLEXIBILITY AND ORGANIZATIONAL PERFORMANCE (STUDY OF MANAGEMENT INFORMATIONS SYSTEMS LITERATURE) - Bimaruci Hazrati Havidz, Hazimi; Mahaputra, M. Rizky (Dinasti Publisher, 2020)
This article discusses literature review studies of Business Information Systems, analyzing factors that affect IT infrastructure: Software, IT Flexibility and Organizational Performance. The method of writing this article is literature study or library research. The results are that: 1) Software has a relationship and affects the IT infrastructure; 2) IT flexibility has a relationship and affects the IT infrastructure; and 3) Organizational performance has a relationship and affects the IT infrastructure.